(3fgL GdHdGZIs - (3Ydj Hf CHj WGdH,J (B40 (3g` s ((3Ydj Hf CHj GdbGSe Hf Ydj GdMGL s)
(3ChdgG (B:s
(3hef NWHg dg Ydjg GdSdGe(B: (3oQhi Cf UGMHkG dCejQ GdeDefjf Ydjg GdSdGe jbGd dg geGe, cGf QLdkG YGHOkG s
(3BNQgG (B:s
(3heG YSGg Cf jXgQ dfG HYV GdZehV, hjbY EdjfG HYO GdTPhP heG JhajbfG EdG HGddg hPdc aj QLH SfI CQHY eFg BNQ cJGH fgL GdHdGZI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B92 - (3U(B174s
(3GdfSNI HgG MhGTs
(3fSNI JGSYIs
(3Gdeced ddLRA GdChd GdSGHb HQbe (B4 (3COH fKQ (B1 (3djJhf LGeYI YdjcQI heYGQVI HGdCUds
(3Hjf SWhQgG hYdi ghGeTgG eYGf hTQhM s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
Keywords: (3GdCOHs